Web-Based Tourism Information System for Pasuruan Regency Destinations - Alan Budi Kusuma Kusuma; Ade Eviyanti; Mochamad Alfan Rosid Rosid; Azmuri Wahyu Azinar Azinar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid advances in information technology enable regions to disseminate tourism information through accessible digital platforms. Specific Background: Pasuruan Regency possesses diverse natural, cultural, culinary, and religious attractions but lacks an integrated system that presents comprehensive and user-participatory tourism data. Knowledge Gap: Previous tourism information systems mainly provided static information without community contribution and administrative validation features. Aims: This study develops a web-based tourism information system that allows users to submit destination data subject to admin verification. Results: The system was built using the waterfall method, successfully passed black-box testing with fully valid functions, and achieved a System Usability Scale score of 68.75, categorized as grade C (acceptable). Novelty: The platform integrates public participation in destination submission with an admin validation workflow within a structured tourism database. Implications: The system provides an accessible medium for tourists and supports local authorities and communities in disseminating tourism information to broaden visitor reach and regional economic activity.